Bending Performance of Steel/CFRP Plate-Reinforced Core Timber Beams - Xiong, X.Y.; Wang, Y.Q.Z.; Lu, X.X.; Xue, R.J. (Проблемы прочности, 2017)
Experimental study and theoretical analysis on flexural behaviour of four core timber beams (one is unreinforced, three are reinforced with steel/CFRP plate) have been conducted. The experimental results show that the bearing capacity of core timber beams reinforced with steel/CFRP (carbon fiber reinforced plastics) plate can be increased by 67.5~97.1% and exhibit higher stiffness, as compared with the unreinforced ones. On this basis, three kinds of failure modes of core timber beams reinforced with steel/CFRP plate are discussed, namely: wood fiber tensile failure, wood fiber compression failure and carbon fiber plate tensile failure. For different failure modes, the compression steel plate yield is cons'idered to derive the formula for calculating the bending capacity of core timber beams reinforced with steel/ CFRP plate. The values calculated by the proposed formula are in good agreement with the experimental results, and, thus, can be applied to the engineering practice.